PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA - Nurhidayah, Rina Suryati; Kurnia, Dadang; Sudin, Ali (Jurnal Pena Ilmiah, 2017)
This research is doing based on lower study result at the material etnic and culture variation, class IV-A SDN Sindang II Sumedang. It is caused by the teacher performance at the implementation only use conventional method and no use media, that have the impact to learning result and student activity the class. The action is done based on effort that overcome set of problem by apply a cooperative learning type make a match. The aim of this research is to describe how to plan, apply, student activity and upgrading study result. This research is doing 3 cycle. The student study result that complete at the cycle 1 as much as 35%, cycle 2 65%, and cycle 3 85%. The target is determined as much as 85% with the result that could be said that application model cooperative type make a match could increase the result learning of student.